The Case of "Kim": The Feelings and Experiences of a Bulimic - Maddocks, Kathyrn M.; Bachor, Dan G. (Canadian Journal of Counselling and Psychotherapy, 2011)
In this paper the case of "Kim" (a pseudonym) is used to illustrate the main characteristics of a bulimic. To illustrate this eating disorder and Kim's feelings and experiences about it, representative excerpts are taken from a series of interviews with her. Kim is followed through the process of learning to vomit, deciding to seek help, and through therapy sessions.